Molecular imprinting as a simple way for the long-term maintenance of the stemness and proliferation potential of adipose-derived stem cells: an in vitro study. Issue 35 (1st July 2022) - Nazbar, Abolfazl; Samani, Saeed; Yazdian Kashani, Sepideh; Amanzadeh, Amir; Shoeibi, Shahram; Bonakdar, Shahin
Abstract : Culturing adipose-derived stem cells (ADSCs) on the biomimetic ADSC-imprinted substrate is a simple way for long-term maintenance of their stemness and proliferation potential. Abstract : Cells are smart creatures that respond to every signal after isolation and in vitro culture. Adipose-derived stem cells (ADSCs) gradually lose their characteristic spindle shape, multi-lineage differentiation potential, and self-renewal ability, and enter replicative senescence after in vitro expansion. This loss of cellular function is a serious impediment to clinical applications that require huge numbers of cells. It has been proven that substrates with cell imprints can be applied for stem cells' differentiation into desired cells or to re-culture any cell type while maintaining its ordinary activity. This study demonstrated the application of cell-imprinted substrates as a novel method in the long-term expansion of ADSCs while maintaining their stemness. Here we used molecular imprinting of stem cells as a physical signal to maintain stem cells' stemness. First, ADSCs were isolated and cultured on the tissue culture plate. Then, cells were fixed, and stem cell-imprinted substrates were fabricated using PDMS. Afterward, ADSCs were cultured on these substrates and subjected to osteogenic and adipogenic differentiation signals. The results were compared with ADSCs cultured on a polystyrene tissue culture plate and non-patterned PDMS. Morphology analysis with optical and fluorescence microscopy and SEM images illustrated that ADSCs seeded on imprinted substrates kept ADSC morphology. Alizarin Red S and Oil Red O staining, flow cytometry, and qPCR results showed that ADSC-imprinted substrates could reduce the differentiation of stem cells in vitro even if the differentiating stimulations were applied. Also, cell cycle analysis revealed that ADSCs could maintain their proliferation potential. So this method can maintain stem cells' stemness for a long time and reduce the unwanted stem cell differentiation that occurs in conventional cell culture on tissue culture plates.